Evaluation of the effectiveness of kinesio taping application in a patient with secondary lymphedema in breast cancer: a case report - Taradaj, Jakub; Halski, Tomasz; Zduńczyk, Małgorzata; Rajfur, Joanna; Pasternok, Małgorzata; Chmielewska, Daria; Piecha, Magdalena; Kwaśna, Krystyna; Skrzypulec-Plinta, Violetta (Menopause Review/Przegląd Menopauzalny, 2014)
Breast cancer-related lymphedema is one of the complications resulting from treatment. It is defined as arm oedema in the breast cancer patients caused by interruption of the flow of the axillary lymphatic system from surgery or radiation therapy, which results in the accumulation of fluid in the subcutaneous tissue of the arm, with a decrease in tissue distensibility around the joints and an increased weight of the extremity. Decongestive lymphatic therapy is common management for lymphedema. A program combining skin care, manual lymphatic drainage, exercise, and compression therapy (multilayer bandage or garment) is recognised as the best practice in lymphedema management. Kinesio taping (KT) for lymphatic drainage is a new choice in the field of physical therapy. The material and the original concept of the taping technique were introduced by Dr Kenso Kase in 1973. K-tape had been designed to allow 30-40% longitudinal stretch. It is composed of 100% cotton fibers and acrylic heat sensitive glue. Development of the technique for its administration is still ongoing. The paper discusses the case of a woman with breast cancer, in whom lymphedema occurred. The patient had three weeks of therapy. The treatment consisted of 12 manual lymphatic drainage, 12 pneumatic compressions and 3 applications of the KT method (due to the lack of standard multi-layer bandaging). During the measurement of oedema it was noted that KT had a significant effect on the reduction of lymphedema and accelerates healing effects compared to standard methods.